The Innovation of Gender Mainstreaming Implementation: A Study on Gender Festival at the Ministry of Environment and Forestry - Nurfathurrohman, Muhammad; Nurhaeni, Ismi Dwi Astuti (Journal of Governance and Public Policy, 2024)
Government agencies need to carry out public policy innovations to deal with changes that occur quickly and dynamically. The Ministry of Environment and Forestry (MoEF) developed an innovation called the Gender Festival as an effort to transform a "Gender Neutral" work environment into a "Nature Gender." This study, therefore, aims to evaluate the fulfillment of innovation aspects and the obstacles encountered in the Gender Festival by using the Australian Public Sector Innovation Indicators (APSII) theory. This qualitative-descriptive research collected data through interviews and documentation data. Data were then analyzed using Miles and Huberman's interactive analysis. The study findings demonstrated that the Gender Festival fulfilled 12 of the 15 aspects of innovation based on the APSII criteria. They comprise investment in innovation, human resources and skills innovation, staff attitudes and attributes for innovation, sources of innovation, technological infrastructure for innovation, diffusion of innovation, innovation culture and leadership, innovation strategy, activities and implementation, types of innovation, innovation novelty, and intangible outputs. On the other hand, the obstacle to implementing a Gender Festival was the limited number of human resources with sufficient capacity to understand gender in managing the workload, which is quite heavy; as a result, innovation collaboration, innovation management practices, and innovation intensity could not be implemented.